PENDELEGASIAN WEWENANG DALAM MENEGAKAN PERATURAN DAERAH NOMOR 4 TAHUN 2013 TENTANG PELARANGAN PEREDARAN DAN PENJUALAN MINUMAN BERALKOHOL DI KOTA CIREBON (STUDI KASUS SATUAN POLISI PAMONG PRAJA KOTA CIREBON) - Mey Luvita; Rahmat Hidayat; Iskandar Zulkarnaen (Universitas Swadaya Gunung Jati, 2017)
ABSTRACTDelegation of authority is a right or power of the leadership of subordinates to carry out her duties and requested accountability for the completion of these tasks Civil Service Police Unit is the local technical institute, who are the delegates as enforcement of local regulations No. 4 of 2013 on the prohibition of the distribution and sale of alcoholic beverages in the city of Cirebon. Some problems in the implementation of delegation of authority is still their circulation and sale of alcoholic beverages from class A to class c well supplied and sold in karaoke entertainment venues, cafes, shops and agents.In this study the author uses the theory of the Delegation of Authority proposed by Manullang in his book entitled